The Role of Neurofeedback in the Treatment of Post-traumatic Stress Disorder: A Neuro Psychological Perspective - Mujahidah, Mujahidah; Marlina, Elly; Aini, Amalia Nur; Hasnawati, Sri; Harahap, Aprilinda M (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Background: Post-Traumatic Stress Disorder (PTSD) treatment using neuropsychology has come a long way. Neurofeedback, also called EEG biofeedback, is a technique that teaches the brain to regulate its own electrical activity. Using an EEG, or electroencephalogram, device, one can see brain activity in real-time and be trained to change unbalanced or abnormal brain wave patterns. Research Purposes: This study was conducted to determine the purpose of neurofeedback, which serves to control this brain activity in a way that is comfortable and suited to the individual. During a neurofeedback session, people usually sit in front of a computer screen and see how their brain activity is depicted. Repetitive training can teach the brain to keep doing healthier activities, even after the therapy session. Method: The method used by researchers in examining the Role of Neurofeedback in the Treatment of Post-Traumatic Stress Disorder: A Neuro Psychological Perspective is to use quantitative methods. The data obtained by researchers were obtained from the results of distributing questionnaires. The questionnaire distribution carried out by researchers was carried out online by utilizing Google From software. The results of the data acquisition will also be tested again using the SPSS application. Results: From the results of the study, it can be seen that from a neuropsychological perspective, neurofeedback aids the restoration of healthy brain function through repeated and consistent learning. This process is known as neuroplasticity, where the brain reshapes and strengthens neural connections made by new experiences and practice. Therefore, neurofeedback not only reduces PTSD symptoms, but also aids in long-term recovery and improves one's quality of life. Conclusion: Researchers can conclude that from a neuropsychological point of view, neurofeedback is not only considered as a therapeutic tool, but also as an entry point to understanding and modulating human brain function during recovery from trauma. Neurofeedback also offers an innovative and science-based approach in the treatment of PTSD, potentially expanding the therapeutic options available to individuals experiencing this disorder.